Kepler-62: A Five-Planet System with Planets of 1.4 and 1.6 Earth Radii in the Habitable Zone - Borucki, William J.; Kaltenegger, Lisa (Science, 2013)
Two Small Habitable Planets - NASA's Kepler space telescope was launched in 2009 with the goal of detecting planets the size of Earth in the habitable zone of Sun-like stars and determining the frequency of these planets. Using data from Kepler, Borucki et al. (p. 587, published online 18 April) report the detection of a five-planet system where all the planets are smaller than twice the size of Earth and where the two outermost planets orbit in the habitable zone of their star, defined as the region where a rocky planet can host liquid water on its solid surface. The star, Kepler-62, is smaller and cooler than the Sun. - We present the detection of five planets—Kepler-62b, c, d, e, and f—of size 1.31, 0.54, 1.95, 1.61 and 1.41 Earth radii (R⊕), orbiting a K2V star at periods of 5.7, 12.4, 18.2, 122.4, and 267.3 days, respectively. The outermost planets, Kepler-62e and -62f, are super-Earth-size (1.25 R⊕ < planet radius ≤ 2.0 R⊕) planets in the habitable zone of their host star, respectively receiving 1.2 ± 0.2 times and 0.41 ± 0.05 times the solar flux at Earth’s orbit. Theoretical models of Kepler-62e and -62f for a stellar age of ~7 billion years suggest that both planets could be solid, either with a rocky composition or composed of mostly solid water in their bulk. - The Kepler mission detected a five-planet system with two small planets in the habitable zone of a star lighter than the Sun. - The Kepler mission detected a five-planet system with two small planets in the habitable zone of a star lighter than the Sun.